2019
DOI: 10.1038/s41467-019-09519-w
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in ensembles of global biodiversity scenarios

Abstract: While there is a clear demand for scenarios that provide alternative states in biodiversity with respect to future emissions, a thorough analysis and communication of the associated uncertainties is still missing. Here, we modelled the global distribution of ~11,500 amphibian, bird and mammal species and project their climatic suitability into the time horizon 2050 and 2070, while varying the input data used. By this, we explore the uncertainties originating from selecting species distribution models (SDMs), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
289
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(338 citation statements)
references
References 29 publications
6
289
1
1
Order By: Relevance
“…There are a number of modelling approaches available for SDM studies including classification, regression, and machine learning methods. To reduce the model-based uncertainty and produce reliable predictions, the ensemble modelling technique has been proposed and frequently used, which combines prediction results of multiple modelling algorithms thus can reduce the uncertainties in model predictions (Araújo & New, 2007;Guisan et al, 2017;Thuiller et al, 2014Thuiller et al, , 2019. Previous studies have revealed that different single modelling algorithms have different predictive ability and can produce largely variable results (Elith & Graham, 2009;Pearson et al 2006;Qiao et al, 2015).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of modelling approaches available for SDM studies including classification, regression, and machine learning methods. To reduce the model-based uncertainty and produce reliable predictions, the ensemble modelling technique has been proposed and frequently used, which combines prediction results of multiple modelling algorithms thus can reduce the uncertainties in model predictions (Araújo & New, 2007;Guisan et al, 2017;Thuiller et al, 2014Thuiller et al, , 2019. Previous studies have revealed that different single modelling algorithms have different predictive ability and can produce largely variable results (Elith & Graham, 2009;Pearson et al 2006;Qiao et al, 2015).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
“…It has been revealed that high uncertainties in future projections of species distributions would arise from differences among GCMs (Goberville, Beaugrand, Hautekèete, Piquot, & Luczak, 2015;Tang et al, 2018;Thuiller et al, 2019). Therefore, it is recommended that used as future climates which is believed to reduce uncertainties associated with different GCMs (Yan et al, 2017).…”
Section: Potential Distributions Under Current and Future Climate Smentioning
confidence: 99%
“…see Barbosa, Estrada, Márquez, Purvis, & Orme, 2012;Fourcade, 2016;Herkt et al, 2017;Meyer et al, 2015), coming to mixed conclusions; however, EOO range maps are still widely used in macroecological research (Belmaker & Jetz, 2015;Hof et al, 2018;Slavenko & Meiri, 2015;Thuiller et al, 2019;Torres-Romero & Olalla-Tárraga, 2015;Zurell et al, 2018). see Barbosa, Estrada, Márquez, Purvis, & Orme, 2012;Fourcade, 2016;Herkt et al, 2017;Meyer et al, 2015), coming to mixed conclusions; however, EOO range maps are still widely used in macroecological research (Belmaker & Jetz, 2015;Hof et al, 2018;Slavenko & Meiri, 2015;Thuiller et al, 2019;Torres-Romero & Olalla-Tárraga, 2015;Zurell et al, 2018).…”
Section: Future Pat Tern S Of S Pecie S Richne Ssmentioning
confidence: 99%
“…Altitudinal midpoint correlated F I G U R E 3 Relationship between raw mean difference (D, %) and species midpoint of altitude (a), IUCN categories of extinction risk (b) and clutch size (c) for atmospheric-ocean global circulation models projections of UKMO. Our estimates of variation in range shifts are likely to be conservative because a recent study by Thuiller et al (2019) showed that ENMs differ greatly in predicting future distributions even when only ENMs with high predictive accuracies are considered in the analyses. Fitted lines represent partial effects of each moderator variable on D positively with differences in range of occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Diniz-Filho et al (2009) showed that the estimated shifts in species' geographic ranges varied broadly, mainly due to the use of different Ecological Niche Models (ENMs hereafter). Furthermore, the characteristics of the modeled organisms (e.g., life history and dispersal ability) can also influence model outcomes (Buisson, Thuiller, Casajus, Lek, & Grenouillet, 2010;Lawler et al, 2010;Thuiller, Guéguen, Renaud, Karger, & Zimmermann, 2019). In other words, different model projections are obtained when different combinations of ENMs, GES, and AOGCMs are used.…”
mentioning
confidence: 99%